The Implementation Of Animated Videos In Enhancing Positive Discipline In Early Childhood - Rezeki, Afriya Sri; Utami, Rahayu Dwi (Riwayat: Educational Journal of History and Humanities, 2025)
This study discusses the application of animated videos in improving positive discipline in early childhood at RA As-syafiiyah Medan Johor. This study aims to improve positive discipline in early childhood through the application of animated videos. The method used in this study is classroom action research using two cycles. The results of the study in cycle I with II meetings in improving positive discipline through the application of animated videos in early childhood showed that 35% of children began to develop (MB), 20% developed according to expectations (BSH), and 10% of children developed very well (BSB). The results of the study in Cycle II with II meetings obtained the final results of 15% of children Developing According to Expectations (BSH), and 85% of children Developing Very Well (BSB), so that the application of animated videos can improve children's positive discipline.